2017
DOI: 10.1002/cpt.936
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, and Proposed Dosing of the Oral JAK1 and JAK2 Inhibitor Baricitinib in Pediatric and Young Adult CANDLE and SAVI Patients

Abstract: Population pharmacokinetic (popPK) modeling was used to characterize the PK profile of the oral Janus kinase (JAK)1/JAK2 inhibitor, baricitinib, in 18 patients with Mendelian interferonopathies who are enrolled in a compassionate use program. Patients received doses between 0.1 to 17 mg per day. Covariates of weight and renal function significantly influenced volume-of-distribution and clearance, respectively. The half-life of baricitinib in patients less than 40 kg was substantially shorter than in adult popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 37 publications
3
99
1
6
Order By: Relevance
“…Interferonopathies represent a collection of both acquired and inherited disorders characterized by overproduction of IFNs. Genetic disorders included among the interferonopathies have been treated with jakinibs with positive results . However, higher doses are required to control symptoms in these patients and treatment has been associated with BK viremia, presumably related to over‐immunosuppression .…”
Section: A Brief Survey Of Approved and Late Phase Jakinibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interferonopathies represent a collection of both acquired and inherited disorders characterized by overproduction of IFNs. Genetic disorders included among the interferonopathies have been treated with jakinibs with positive results . However, higher doses are required to control symptoms in these patients and treatment has been associated with BK viremia, presumably related to over‐immunosuppression .…”
Section: A Brief Survey Of Approved and Late Phase Jakinibsmentioning
confidence: 99%
“…Genetic disorders included among the interferonopathies have been treated with jakinibs with positive results. [110][111][112][113] However, higher doses are required to control symptoms in these patients and treatment has been associated with BK viremia, presumably related to overimmunosuppression. 111,113,114 Of interest, it has been proposed that Down syndrome should be classified as an interferonopathy, and jakinibs have been suggested as a possible therapy.…”
Section: Polycythemia Vera and Myelofibrosismentioning
confidence: 99%
“…Since this time, several reports published suggest that the phenotypic spectrum is broad, and the penetrance of disease is variable, with cytopenias, lymphoproliferative disease and immune deficiencies being reported. [113][114][115] Interestingly, some clinical manifestations persist despite treatment. 112 Gain-of-function mutations in TMEM137 encoding the cytosolic innate immune sensor STING result in an autoinflammatory disease characterised by peripheral vascular inflammation, nail dystrophy and interstitial lung disease termed STING associated vasculopathy with onset in infancy (SAVI).…”
Section: Vasculitismentioning
confidence: 99%
“…113 Like Deficiency of ADA2, patients with SAVI have an interferon gene signature but in this disorder, it appears to be causing, at least in part, clinical disease as evidenced by the response to Janus kinase (JAK)/STAT inhibition. [113][114][115] Interestingly, some clinical manifestations persist despite treatment. For example, the lividinous rash in one case did not respond to ruxolitinib, suggesting that the interferon pathway may not be the only pathway involved in disease.…”
Section: Vasculitismentioning
confidence: 99%
“…Some studies showed that baricitinib was safe and well tolerated following treatment of patients with moderate to severe RA for 24 weeks [8,15,16]. However, other studies demonstrated that baricitinib induces a stable dose-response increase in LDL-C and HDL-C levels with developing the risk of thrombosis [17], elevates infection risk, particularly for herpes zoster [18] and GI perforations [19]. Substantial data concerning baricitinib embryotoxicity and teratogenicity in humans are lacking.…”
Section: Introductionmentioning
confidence: 99%